Spiritual Healing with Aswaja Ruqyah: A Quranic-Based Non-Medical Approach - Nabilla Azzahra; Althaf Husein Muzakky; Muhammad Misbah (UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to explore the effectiveness of Aswaja ruqyah therapy in addressing non-medical disorders, particularly those related to psychological issues such as stress, anxiety, and emotional disturbances. The method used is a qualitative approach involving in-depth interviews with patients undergoing ruqyah therapy, as well as observations of the therapeutic practices. The results of the study indicate that Aswaja ruqyah therapy has a positive impact on mental and emotional well-being, with many patients reporting feelings of greater calmness and a reduction in anxiety symptoms. This study recommends the implementation of ruqyah therapy as an alternative in non-medical treatment to support community mental health. In conclusion, Aswaja Ruqyah is effective as a spiritual therapy that can aid emotional and psychological recovery and is acceptable within a more holistic treatment context.